Preoperative Left Ventricular Remodeling Based on Echocardiographic Findings in Patients with Ischemic Mitral Regurgitation - Rudenko, S. A.; Potashev, S. V.; Verich, N. M. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Ischemic mitral regurgitation (IMR) is a dynamic phenomenon depending on myocardial function and he- modynamics. Grade, hemodynamic significance and anatomic reasons of IMR are always key features for defining indica- tions for surgical treatment. In chronic IMR diagnosis, the emphasis is upon mitral regurgitation (MR) mechanisms and its hemodynamic consequences. The aim. To study preoperative echocardiographic features of left ventricular (LV) remodeling and IMR, and retro- spectively define their influence upon the choice of IMR surgical correction method. Materials and methods. We performed surgical correction of IMR in 292 patients over the period from January 2012 to December 2019 at the National Amosov Institute of Cardiovascular Surgery. All the patients were divided into 2 groups depending on MR surgical correction method. Group 1 included 141 patients who underwent valve-sparing sur- gery. Group 2 included 151 patients after prosthetic mitral valve replacement. All the patients underwent comprehensive echocardiography prior to surgery. Results and discussion. The patients of Group 2, who underwent prosthetic mitral valve replacement showed sig- nificantly more marked eccentric LV remodeling, namely significantly higher LV EDI (p=0.02) and ESI (p=0.0027) with significantly worse LV global contractility: compared to Group 1, almost twice bigger proportion of patients in Group 2 had severely decreased LVEF ≤30% (p=0.047), while mean LVEF corresponded with moderate LV systolic dysfunc- tion (LVEF≤45%), and in Group 1 the majority of patients had mild-to-moderate LV systolic dysfunction (LVEF ≥45% and ≥35%, respectively, p=0.016) with significantly higher proportion of patients with preserved LVEF (p=0.039). This caused marked remodeling in Group 2 patients, lead to impossibility of valve-sparing MV plastics and brought up neces- sity of prosthetic MV replacement, which is aligned with available evidence on poor prognosis markers and reverse left chambers remodeling in functional secondary MR, including IMR. Conclusions. Significantly more marked LV remodeling and more severe systolic dysfunction lead to more severe IMR with more marked MV valvular morphology alterations and more frequent MV replacement. Our data witness in favor of earlier surgical intervention in coronary artery disease (CAD) patients with IMR aiming at successful valve-sparing IMR correction.